A constructivist account of the post cold war role of the European Union in the Israel-Palestinian conflict - Söyler, Mehtap (My University, 2004)
A CONSTRUCTIVIST ACCOUNT OF THE POST COLD WAR ROLE OF THE EUROPEAN UNION IN THE ISRAELI-PALESTINIAN CONFLICT This thesis endeavours at explaining to what extent the EU could transfer international and societal norms it pursues to the protractors of the Israeli-Palestinian conflict during Post-Cold War period by utilising constructivist terms. Accommodation of Israeli and Palestinian people with international normative institutions through their interaction with EU had to confront societal norms of the protractors and other major actors of international system. While capturing historical turns of norm change in the conflict and the role of the EU in norm change, this study claims that unlike propositions of 'EU as a payer to the peace process', the course of the conflict proves that EU has in its tacit way influenced the agenda of the process during the Post Cold War period.

AVRUPA BİRLİĞİ'NİN İSRAİL-FİLİSTİN ÇATIŞMASINDA SOĞUK SAVAŞ SONRASI ROLÜNÜN YAPILANDIRMACI ANLATIMI Bu tez AB'nin kendi uluslararası ve toplumsal normlarını Soğuk Savaş sonrasında İsrail-Filistin çatışmasının taraflarına ne ölçüde transfer edebildiğini, yapılandırmacı teorinin terimlerinin kullanılarak anlatımını amaçlamaktadır. İsrail ve Filistin halklarının AB ile etkileşimleri sonucu uluslararası normatif kurumlara uyumu, AB normlarını ve çatışmanın taraflarının ve uluslararası sistemin diğer önemli aktörlerinin sahip oldukları toplumsal normlarla karşı karşı karşıya getirmiştir. Bu çalışma, çatışmadaki tarihsel norm değişikliği dönemlerini ve AB'nin bu değişikliklerdeki rölünü kavrarken, 'AB'nin barış sürecinin bir ödeyicisi' olduğunu iddia eden görüşlerin aksine, AB'nin Soğuk Savaş sonrası süreçte gündemi dolaylı yoldan etkilediğini gösterdiğini ortaya koymaktadır.
Keywords: Avrupa Birliği; Filistin _Dış İlişkiler_İsrail; İsrail_ Dış İlişkiler_Filistin